PERKEMBANGAN MEDIA PEMBELAJARAN KINCIR CIPURAK (KARAKTERISTIK PUISI RAKYAT) MATERI PUISI RAKYAT KELAS VII MTS AL-MUHTADUN JABUNG TALUN BLITAR - Nurani, Aldina Dwi; Hermawan, Agus; Hadi, Saptono (Yayasan Amanah Nur Aman, 2025)
This research is based on the challenges faced by grade VII students in understanding folk poetry materials, including rhymes, poems, and gurindam, often due to less interesting learning approaches and the absence of adequate interactive media. To overcome these problems, development research is carried out to produce learning media that is relevant and can facilitate student understanding. The 4D development method (Define, Design, Develop, Disseminate) was chosen as the framework for this research. The implementation of the learning media named